Neuropedagogy and Neuroimaging of Artificial Intelligence and Deep Learning - Claudia De Barros Camargo , Antonio Hernández Fernández (Educational Process: International Journal)
Background/Purpose. This study investigates the integration of neuropedagogy, neuroimaging, artificial intelligence (AI), and deep learning in educational systems. The research aims to elucidate how these technologies can be synergistically applied to optimize learning processes based on individual neurocognitive profiles, thereby enhancing educational effectiveness.